The results of surgical treatment of giant cell tumor of long bones - Diedkov, Anatolii; Maksymenko, Bogdan; Boychuk, Sergii; Kostiuk, Viktor; Kukuskina, Maria (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2023)
The standard treatment option for Giant cell tumor (GCT) is surgery. The radical resection followed by reconstruction is associated with definite clinical problem: high rate of complications, reducing of limb function. Tumor excohleation allows to preserve the joint, but has a high rate of local recurrence. Objective: in retrospective study to analyze the advantages and disadvantages of intralesions and wide radical resection based on results of treatment in patients with Giant cell tumor. Methods: we performed a retrospective analysis of treatment results of 142 patients with long bones Giant cell tumor in the period from 1977 to 2012 years. Tumor excohleation (intralesional resection, IR) with grafting the defect with bone or biodegradable materials was performed in 70 cases, wide resections (WR) with defect reconstructions — in 72 patients. Results: in the group of patients who underwent IR the local relapses were revealed in 35.7 % of cases, which is seven times higher than in WR group. Functional result according to MSTS scale in patients after IR was 92.5 %, after WR — 78.8 % (p = 0.02). Such clinical factors as IR, localization of tumor in the distal radius, age under 25 years is strongly associated with appearence of local recurrence. For patients after IR PFS was 71.0 %, after WR — 95.8 % (p = 0.001). Conclusions: the optimal surgical method in patients with Giant cell tumor of long bones is IR due to good functional results. However, local relapse rate in this group remains high — 35.7 % versus 4.5 % in group after WR (p < 0.05). One of the way of its reducing is application of new therapeutic agents e. g. denosumab, the effectiveness of which can be assessed in prospective trials.